Students’ Perception on Academic Dishonesty in a Senior High School - Fadila, Safira Ardya Pelita (English Education Department, Universitas Islam Indonesia, 2022)
This study aims to identify students’ perceptions and knowledge related to Academic Dishonesty (AD), specifically plagiarism and cheating. This is a survey study. The data were collected using an adapted questionnaire developed by Ledesma (2011); the data were gathered from students whose school applies academic integrity as the basic rules. Nine statements in four domains are included in the questionnaire. Non-probability sampling technique was used in this survey study by involving 122 respondents from various senior high schools. The result shows that students do not perceive Academic Dishonesty (AD) as misconduct. Out of 9 examples of AD, most of the participants agree that cheating is only when they copy their peers’ exact answers on a certain test. Meanwhile, they tend to discount other statements as a form of AD. This research could be an underlying base for stakeholders to know the students’ perception of AD, which eventually will help implement the Indonesia Ministry of Education’s character-building program.